Effectiveness of Supportive Therapy in Reducing Anxiety in Adolescents in Sukamaju Village, Purwakarta - Pratiwi, Shinny Ria (CV. Publikasi Indonesia, 2025)
Anxiety disorders among adolescents have become a significant public health concern, particularly in rural communities where access to mental health services is limited. Supportive therapy represents a viable intervention approach that can be implemented in community settings. This study aimed to evaluate the effectiveness of supportive therapy in reducing anxiety levels among adolescents in Sukamaju Village, Purwakarta. A quasi-experimental design was employed with 60 adolescents aged 12-18 years experiencing anxiety symptoms. Participants were divided into intervention and control groups. The intervention group received 8 sessions of supportive therapy over 4 weeks, while the control group received standard care. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HAM-A) before and after intervention. The intervention group showed significant reduction in anxiety scores (pre-test: 18.5±3.2, post-test: 12.3±2.8, p<0.001) compared to the control group (pre-test: 18.1±3.5, post-test: 17.2±3.1, p>0.05). The effect size was large (Cohen's d = 2.1), indicating clinically significant improvement. Supportive therapy demonstrated significant effectiveness in reducing anxiety among adolescents in rural community settings, suggesting its potential as a feasible mental health intervention for underserved populations.